Neurovascular Unit: Basic and Clinical Imaging with Emphasis on Advantages of Ferumoxytol. Issue 6 (June 2018) - Netto, Joao Prola; Iliff, Jeffrey; Stanimirovic, Danica; Krohn, Kenneth A; Hamilton, Bronwyn; Varallyay, Csanad; Gahramanov, Seymur; Daldrup‐Link, Heike; d'Esterre, Christopher; Zlokovic, Berislav; Sair, Haris; Lee, Yueh; et al.
N/A: N/A: Physiological and pathological processes that increase or decrease the central nervous system's need for nutrients and oxygen via changes in local blood supply act primarily at the level of the neurovascular unit (NVU). The NVU consists of endothelial cells, associated blood‐brain barrier tight junctions, basal lamina, pericytes, and parenchymal cells, including astrocytes, neurons, and interneurons. Knowledge of the NVU is essential for interpretation of central nervous system physiology and pathology as revealed by conventional and advanced imaging techniques. This article reviews current strategies for interrogating the NVU, focusing on vascular permeability, blood volume, and functional imaging, as assessed by ferumoxytol an iron oxide nanoparticle.